Ba6In6Zn4Se19: a high performance infrared nonlinear optical crystal with [InSe3]3− trigonal planar functional motifs. Issue 23 (19th May 2020) - Zhou, Anyi; Lin, Chensheng; Li, Bingxuan; Cheng, Wendan; Guo, Zhengxiao; Hou, Zhufeng; Yuan, Fangyu; Chai, Guo-Liang
Abstract : A new crystal Ba6 In6 Zn4 Se19 with a trigonal planar functional motif [InSe3 ] 3− is synthesized and shows well-balanced NLO performance. Abstract : An excellent nonlinear optical (NLO) material should satisfy many critical requirements simultaneously. How to balance all the requirements is a challenge, as they cause contradictory demands on structural attributes. Here, we use a high entropy strategy to integrate the advantages of ZnSe for a large NLO coefficient and a planar [InSe3 ] 3− functional motif for phase matching. The resulting Ba6 In6 Zn4 Se19 crystal shows excellent comprehensive NLO properties, i.e. a large effective NLO coefficient (2 × AgGaS2 ), a high laser induced damage threshold (LIDT, 15.5 × AgGaS2 ), a wide transmission range (0.52–22.5 μm), and an increased birefringence (Δ n = 0.098) for phase matching. Theoretical calculations indicate that planar [InSe3 ] 3− is an effective NLO functional motif for tuning birefringence and the "cocktail effect" realized via the high entropy strategy is important to improve the overall NLO performance. This study provides a promising way of developing new NLO materials with excellent comprehensive performance.